Consumo alimentar por indivíduos em tratamento de obesidade: uma análise sob a ótica da teoria das práticas - Gomes, Roberta Pacheco (2024)
The overall objective of this research is to investigate changes in the dietary consumption practices of individuals undergoing obesity treatment. Considering the epidemic and growing proportion of obesity in the global population, particularly alarming numbers in Brazil, as well as the relevance of healthy dietary consumption in combating non-communicable chronic diseases (NCDs), this study seeks theoretical and empirical information to fulfill the proposed objective. It is grounded in the theory of practices, which proves valuable for analyzing consumption and NCDs. A theoretical framework was developed on the relationship between the theory of practices, consumption, and dietary consumption practices, enabling the capture of changes in practice before and during obesity treatment across four dimensions: the three analytical variables of dietary consumption practice; dietary consumption practice composed of its integrative practices; elements of dietary consumption practice; and the three fundamental dimensions of consumption arising within and because of practices. Regarding the methodological aspects, a qualitative and interpretative approach was chosen. Data were collected through semi-structured interviews with individuals ndergoing obesity treatment who maintain controlled obesity, aiming to compare permanent changes in dietary consumption practices before and during obesity treatment. Content analysis was applied to analyze data, using the same categories as the theoretical framework. Analyses and discussions on the nexus of dietary consumption practices, composed of their elements and integrative practices, elucidate how individuals undergoing obesity treatment transition between practices that kept them obese and those that began after obesity treatment, solidifying a healthier lifestyle. These new arrangements in practice performance also allowed identifying the degree of individuals' involvement with dietary consumption arising within and because of practices. Additionally, the analyses and discussions highlighted contributions to the obesity solutions market in the three pillars of changing dietary consumption practices according to ABESO (2022): behavioral education strategies, nutritional education strategies, and dietary reeducation strategies. Lastly, the research conclusions revealed the individual and social roles in improving dietary consumption practices in combating obesity, as well as providing insights into public policies across various sectors.